Metabolomic Profiling of Infants With Recurrent Wheezing After Bronchiolitis. (16th November 2018) - Barlotta, Alessia; Pirillo, Paola; Stocchero, Matteo; Donato, Filippo; Giordano, Giuseppe; Bont, Louis; Zanconato, Stefania; Carraro, Silvia; Baraldi, Eugenio
Abstract: Background: Bronchiolitis is associated with a greater risk of developing recurrent wheezing, but with currently available tools, it is impossible to know which infants with bronchiolitis will develop this condition. This preliminary prospective study aimed to assess whether urine metabolomic analysis can be used to identify children with bronchiolitis who are at risk of developing recurrent wheezing. Methods: Fifty-two infants <1 year old treated in the emergency department at University Hospital of Padova for acute bronchiolitis were enrolled (77% tested positive for respiratory syncytial virus [RSV]). Follow-up visits were conducted for 2 years after the episode of bronchiolitis. Untargeted metabolomic analyses based on mass spectrometry were performed on urine samples collected from infants with acute bronchiolitis. Data modeling was based on univariate and multivariate data analyses. Results: We distinguished children with and those without postbronchiolitis recurrent wheeze, defined as ≥3 episodes of physician-diagnosed wheezing. Pathway overrepresentation analysis pointed to a major involvement of the citric acid cycle ( P < .001) and some amino acids (lysine, cysteine, and methionine; P ≤ .015) in differentiating between these 2 groups of children. Conclusion: This is the first study showing that metabolomic profiling of urine specimens from infants with bronchiolitis can be used to identify children at increased risk of developing recurrent wheezing. Abstract : Bronchiolitis is associated with the risk of developing wheezing disorders. We found that metabolomic profiling of urine specimens from infants with acute bronchiolitis can be used to identify children who are at risk of developing recurrent wheezing and could benefit from early prevention measures.